Emerging importance of multidrug-resistant Stenotrophomonas maltophilia infections in neonatal intensive care unit in a tertiary center in Turkey - Asuman Demirbuğa; Deniz Bahar Akgün Karapınar; Beril Yaşa; Asuman Çoban; Betigül Öngen; Elif Dede; Neslihan Mete Atasever; Ayper Somer; Selda Hançerli Törün (Elsevier, 2024)
Objective: Stenotrophomonas maltophilia is an emerging multi-drug resistant, opportunistic pathogen in the neonatal intensive care unit (NICU). In this study, we aimed to assess the incidence, clinical features, antibiotic susceptibility, and treatment options of S. maltophilia infection among the healthcare-associated infections (HAIs) in the neonatal unit. Methods: In this study, the patients who were hospitalized in the NICU between January 2020 and December 2021 with S. maltophilia isolated from clinical samples were included. Demographic, clinic features, and microbiological findings of the patients were retrospectively evaluated by using the medical records. The samples (lower respiratory tract, urine, peritoneal fluid) were first examined microscopically by gram preparation and cultured. Antibiotic susceptibility tests were performed according to the recommendations of The European Committee on Antimicrobial Susceptibility Testing (EUCAST) for TMP-SMX. Results: S. maltophilia was isolated in 38 clinical samples of the 20 patients who were hospitalized at the NICU between January 2020 and December 2021. A total of 40 % (n = 8) of samples from different patients were accepted as colonization. Ventilator-associated pneumonia was determined in 55 % (n = 11), and urinary tract infection in 5 % (n = 1). S. maltophilia-associated bacteremia was not detected in any of the cases. The TMP-SMX susceptibilities of the strains were as it follows: 3 (15 %) were resistant (R), 7 (28 %) were susceptible (S), and 10 (47 %) were susceptible-increased exposure (I). Three of these patients were given dual antibiotics therapy (levofloxacin plus TMP-SMX) and nine of them were given only TMP-SMX. The most common hospital-acquired infectious agents are Gram negative microorganisms (51 %), followed by coagulase negative staphylococci (CNS), Staphylococcus aureus (24 %) and S. maltophilia (24 %). Conclusion: Increasing TMP-SMX resistance and specific drug and dosage-related problems in the neonatal unit are important problems in treatment management.